Analysis of the Dominant Factors of Flood in Mendalam Sub-Watersheds - Jajaher, Jinau Jacky; Herawati, Henny; Yulianto, Eko (Jurnal Teknik Sipil, 2026)
Flooding is a recurring hydrological problem in the Mendalam Sub-Watershed, Kapuas Hulu Regency, West Kalimantan, resulting in significant socioeconomic and environmental impacts. This study aims to (1) identify flood characteristics, (2) determine dominant hydrological and geomorphological factors contributing to flooding, and (3) evaluate flood discharge variations under different runoff coefficient scenarios. The analysis employs land-cover assessment, slope and soil-type evaluation, rainfall analysis, and factor analysis using the Kaiser–Meyer–Olkin Measure of Sampling Adequacy (KMO-MSA). Secondary data include rainfall records from 2004–2022, DEMNAS topographic data, and land-cover data from 2015, 2018, and 2022, whereas primary data were obtained through field observations and community interviews. Results indicate that slope is the dominant factor influencing flood occurrence, followed by rainfall, soil type, and land-cover change. The analysis also shows that increases in runoff coefficients lead to higher peak flood discharges, indicating the sensitivity of flooding to land-cover changes. These findings highlight the importance of integrated watershed management and land use control as key strategies for flood mitigation in the Mendalam Sub-Watershed.